An Unusual Mishap during Root Canal Access in Retreatment Case. (2nd October 2012) - Hampanna Malur, Manjunath; Krishna, Akash; Sapna, D. V.
Abstract : Varieties of objects have been introduced into the root canal system accidentally or intentionally; removal of these objects necessitates the success of the treatment. This paper explains an unusual bur fracture during nonsurgical endodontic treatment and its removal by ultrasonic energy with ease and without the removal of extra large amount of root dentin.